2012
DOI: 10.3109/00207454.2012.672502
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Cystatin C(CST3) Gene G73A Polymorphism and Susceptibility to Alzheimer's Disease

Abstract: The CST3 G73A polymorphism is associated with AD in Caucasian populations, but not in Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…However, some studies have failed to show an association between CST3 and AD in a German cohort (Dodel et al, 2002), a Dutch sample with early onset AD (Roks et al, 2001), Japanese AD patients (Maruyama et al, 2001), a Finnish population (Helisalmi et al, 2009), and in early onset AD families (Parfitt et al, 1993). Other studies found a connection between the CST3 polymorphism and AD in Caucasian populations, but not in Asian populations (Hua et al, 2012), including Chinese (Wang et al, 2008). Over-all meta-analyses using this polymorphism have reported CST3 as a susceptibility gene for AD.…”
Section: Cysc and Alzheimer's Diseasementioning
confidence: 88%
“…However, some studies have failed to show an association between CST3 and AD in a German cohort (Dodel et al, 2002), a Dutch sample with early onset AD (Roks et al, 2001), Japanese AD patients (Maruyama et al, 2001), a Finnish population (Helisalmi et al, 2009), and in early onset AD families (Parfitt et al, 1993). Other studies found a connection between the CST3 polymorphism and AD in Caucasian populations, but not in Asian populations (Hua et al, 2012), including Chinese (Wang et al, 2008). Over-all meta-analyses using this polymorphism have reported CST3 as a susceptibility gene for AD.…”
Section: Cysc and Alzheimer's Diseasementioning
confidence: 88%
“…It is interesting to note that a polymorphism (G73A) in cystatin C has been linked to AD (43). Furthermore, cystatin C is increased in regions around A␤ deposits in the AD brain (44,45), suggesting that it may play a role in pathogenesis or in response to A␤ pathology.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Cystatin C has also been linked to risk of cognitive impairment in genetic and neuropathological studies. A common polymorphism of the cystatin C gene is associated with greater risk of Alzheimer's disease (AD), [8][9][10] and cystatin C colocalizes with bamyloid in the brain, especially in areas involved in AD pathology. 11,12 Age, sex, and muscle mass affect cystatin C, as a measure of kidney function, much less than serum creatinine.…”
Section: Objectivesmentioning
confidence: 99%